2006
DOI: 10.1186/1465-9921-7-16
|View full text |Cite
|
Sign up to set email alerts
|

EM703 improves bleomycin-induced pulmonary fibrosis in mice by the inhibition of TGF-β signaling in lung fibroblasts

Abstract: Background: Fourteen-membered ring macrolides have been effective in reducing chronic airway inflammation and also preventing lung injury and fibrosis in bleomycin-challenged mice via anti-inflammatory effects. EM703 is a new derivative of erythromycin (EM) without the bactericidal effects. We investigated the anti-inflammatory and antifibrotic effects of EM703 in an experimental model of bleomycin-induced lung injury and subsequent fibrosis in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 49 publications
2
49
0
Order By: Relevance
“…EM703 is a derivate of erythromycin and has been reported to exhibit anti-inflammatory activity independent from anti-bacterial activity by suppressing nuclear factor-κ B and inhibiting interleukin-8 expression (Y. Li et al, 2006). Previously, 14-membered macrolides have been shown to attenuate leukocyte migration in the early inflammatory phase and thereby prevent bleomycin induced lung fibrosis (Y.…”
Section: Em703mentioning
confidence: 99%
See 1 more Smart Citation
“…EM703 is a derivate of erythromycin and has been reported to exhibit anti-inflammatory activity independent from anti-bacterial activity by suppressing nuclear factor-κ B and inhibiting interleukin-8 expression (Y. Li et al, 2006). Previously, 14-membered macrolides have been shown to attenuate leukocyte migration in the early inflammatory phase and thereby prevent bleomycin induced lung fibrosis (Y.…”
Section: Em703mentioning
confidence: 99%
“…The authors concluded that EM703 improves bleomycin-induced pulmonary fibrosis in mice by acting as an antiinflammatory agent and regulating TGF-β signaling (Y. Li et al, 2006).…”
Section: Em703mentioning
confidence: 99%
“…Consistent with that interpretation, antibiotics reduce the rate of aseptic loosening [10,23] and periprosthetic inflammation [89] in patients as well as particle-induced osteolysis in mice [91]. However, those results do not conclusively support the PAMP hypothesis because antibiotics can have antiinflammatory effects that are independent of their bactericidal effects [58,61,90,94]. The PAMP hypothesis depends on the presence of these molecules, at least episodically, during aseptic loosening.…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…3) and whether the reported effects of antibiotics on aseptic loosening [10,23,89,91] are the result of bactericidal effects or the antiinflammatory effects of antibiotics that are independent of bacteria [58,61,90,94]. Further in vivo murine studies are also needed to determine (1) whether PAMPs are required for TLR activation; (2) the roles of pathogen recognition receptors other than TLR2 and TLR4; and (3) the mechanisms responsible for particle-induced osteolysis in the absence of PAMPs.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
See 1 more Smart Citation